2006
DOI: 10.2498/cit.2006.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Transclusions in an HTML-Based Environment

Abstract: Transclusions are an advanced technique for the inclusion of existing content into new documents without the need to duplicate it. Although originally described in the early 1960s, transclusions have still not been made available to users and authors on the world wide web. This paper describes the prototype implementation of a system that allows users to write articles that may contain transclusions. The system offers a simple web-based interface where users can compose new articles. With a simple button the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…We have shown that there are some data structures, indeed relatively simple ones, which cannot be formally modelled using ZigZag, even with the addition of its cloning conventions. Transclusion is a particularly interesting mechanism and yet it is an aspect of hypermedia that has often been neglected (although this is gradually changing with growing interest in implementing it on the web [9], and in resources such as Wikipedia [4]). The analysis described in this paper has revealed that there are important aspects to transclusion that have previously been overlooked.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that there are some data structures, indeed relatively simple ones, which cannot be formally modelled using ZigZag, even with the addition of its cloning conventions. Transclusion is a particularly interesting mechanism and yet it is an aspect of hypermedia that has often been neglected (although this is gradually changing with growing interest in implementing it on the web [9], and in resources such as Wikipedia [4]). The analysis described in this paper has revealed that there are important aspects to transclusion that have previously been overlooked.…”
Section: Resultsmentioning
confidence: 99%
“…As shown by [3] basic Web technologies such as plain HTML, JavaScript, CGI scripts and a specialized HTTP proxy application allow realizing transclusions on the Web.…”
Section: Content Reuse Methodsmentioning
confidence: 99%
“…In [4] authors investigated how to adapt the idea of transclusions to the World Wide Web. They presented a prototype composed of some server-side modules resolving transclusions, and a client-side interface running on Firefox.…”
Section: Related Workmentioning
confidence: 99%